Understanding Feminism Perspective on Informal Women Entrepreneurs in Kyengera Town Council - Henry Stanley, Mbowa; Siraje, Kaaya (International Journal of Research in Sociology and Anthropology, 2020)
The process of marginalization and exclusion from intersectional and multilevel perspectives has much focus on intersectional of ethnic, gender and class background, which all vested in the feminism perspective of informal women entrepreneurs. The purpose of the paper is to examine the philosophical perspectives on informal women entrepreneurs in Uganda with a focus on how epistemological experiences and perspectives influence informal businesses and what the socio-cultural experiences of women entrepreneurs in Kyengera town council are. The paper is guided by a documentary-based review design using mixed methods, and data collected through on desk review from scholarly articles. The paper indicates various philosophical descriptions, epistemological experiences and perspectives and socio-cultural experiences of informal women entrepreneurs in Kyengera Town Council. The paper concludes that, feminist researchers need to focus on mixed methods research as means to address the knowledge, power and gender-gap among informal women entrepreneurs. This should include knowledge and science to constitute inclusion of women to eliminate male-biased ideologies.